THE ACQUISITI ON OF WORDS BY TWO-YEAR-OLD TWIN CHILDREN - Ambarita, Rosmita (LP2M Universitas Muslim Nusantara Al Washliyah, 2018)
This research was conducted to discover the acquisition of words acquired by two-year-old twin children, two females and two males. The two females were Yaya and Tata and the two males were Randy and Rendy. The main objectives of this research are to discover how the number words acquired by two-year-old twin children, to discover who acquires more verbs and nouns among the four subjects and to discover the differences between female and male twin children in acquiring words. The instruments used for data collection were observations and interviews. The observations were conducted for three months, twice a week and interviewing childrenâs parents by asking some questions. The problems of this research were how many verbs and nouns are acquired by two-year-old twin children? Who acquires more words among the four twin children? Is there any difference between female and male twin children in acquiring verbs and nouns? Based on the observations, female children acquired more words than male children, but the male children produced the words clearer than female. Within that period, Yaya obtained 206 words, (134 nouns and 72 verbs), Tata obtained 237 words, (149 nouns and 88 verbs), Randy obtained 227 words, (136 nouns and 79 verbs), Rendy obtained 230 words, (138 nouns and 92 verbs). From all the words which were obtained by the subjects the result showed that nouns dominate the acquisition and the result of the observation Tata was the best in acquiring verbs and nouns among the four subjects.